Currículo vivido: uma nova abordagem das políticas públicas privilegiando projetos inovadores na cidade de São Paulo - Cocco, Cecília Aparecida (2008)
This dissertation analyzes a realized curricular proposition at Vila Prudente/Sapopemba s Governmental Educational Agency systems, of the Municipal Secretary of Education of Sao Paulo, in the period of 2003-2004 (management, 2001-2004), with the title: Vivid Curriculum: a new broach of public policies privileging innovative projects in the city of Sao Paulo. This proposition undertook the school, locus of public policies and the supervising actions, such as a collective effort, supervised by the Accompanying Educational Actions Group (AEAG), constituted on the central nucleus of formation; evaluation and decision of this curricular experience, with the responsibility of involving a scholarly community, segments of the local social movements and a broad in the construction of an innovative curriculum in the Educational Agency, situated in the peripheral zone, east of Sao Paulo. Parting on the hypothesis that it was an innovative proposition for public schools, the search analyzed the documents that constituted this public policy of education, discussed some themes that founded the proposition and the participants discussions, such as public policy, vivid curriculum, democratic management, and supervisory action. It registered decisive moments of this collectively assumed project by the participants and proposed the reencounter of those who actively partook in this process, to evaluate the history, the contradictions and the results. The analysis reunited representatives of scholarly unity, and of the different participating segments of an experience that was undertaken collectively, for the past three years, to analyze this proposition s impacts and perspectives. The collective analysis of the experience, supported the group discussion, in which the actors in the debate, express collective thought, and a common evaluating position of this political curriculum, transcribed in text and registered on DVD, annexed in the text of the dissertation